Blown film extrusion : an introduction - Cantor, Kirk (Hanser Publishers ; Hanser Gardner Publications, 2006)
"From hardware and materials through processing and properties, a broad coverage of blown film extrusion is presented. A primary objective of this book is to ensure a useful balance of theory and practice. The reader will find the answers to "Why?" they encounter certain effects in the blown film process so that they are better able to troubleshoot and improve their operations. At the same time, current practices and equipment are emphasized to keep readers up-to-date with the most productive and efficient technology."--Title details from web site